Nature and incidence of peripheral nerve syndromes in HIV infection. - Fuller, G N (1993)
Fifty four patients with peripheral nerve syndromes were seen during a 15 month period in a population of about 1500 HIV infected patients at all stages of the disease. Distal symmetrical peripheral neuropathies were seen in 38 of the 54 patients, (11.5% of AIDS patients) and could be distinguished into two forms. The most common (n = 25) was a painful peripheral neuropathy during AIDS, which is distinct clinically and pathologically, having axonal atrophy, and is associated with cytomegalovirus infection at other sites. The 13 non-painful neuropathies seen were more heterogeneous. Lumbosacral polyradiculopathy associated with cytomegalovirus and lymphomatous mononeuritis multiplex occurred in fewer than 1% of AIDS patients. Mononeuropathies were seen in 3% of AIDS patients. No patients with acute or chronic inflammatory demyelinating polyradiculoneuropathies were seen. The annual incidence of neuropathies during the AIDS related complex stage was less than 1%; none were seen in asymptomatic HIV seropositive patients.